ANALISIS NILAI DALAM CERITA RAKYAT SUKU TOLAKI PASA’ENO - Kiki Reski Wulandari (Cakrawala Listra: Jurnal Kajian Sastra, Bahasa, dan Budaya Indonesia, 2023)
This research aims to analyze the values ​​in the folklore of the Tolaki tribe "Pasa’eno". The method in this research is to use library research with a qualitative approach. Based on the results of the value analysis in the folklore of the Tolaki Pasa’eno Tribe, several values ​​were found contained in the folklore. Analysis of the values ​​found are religious values, moral values ​​and cultural values. The religious values ​​contained in the text are religious values ​​between fellow humans and their beliefs. Moral values ​​are divided into two, namely moral values ​​related to oneself, namely; hard work, honesty, courage and the value of patience. Moral values ​​related to fellow humans are mutual respect between fellow humans and good prejudice between fellow humans. The cultural value contained is the value of love. Key Words : folklore, value, Pasaeno